Solitaire FR device for treatment of dural sinus thrombosis. (19th December 2012) - Pukenas, Bryan Anthony; Kumar, Monisha; Stiefel, Michael; Smith, Michelle; Hurst, Robert
Abstract : Dural venous sinus thrombosis is a rare and potentially devastating disease. Several predisposing factors exist, including oral contraceptive therapy and colitis. First-line therapy consists of systemic anticoagulation. If first-line therapies fail, more aggressive endovascular therapies may be performed. We report our initial experience with the Solitaire FR device for treatment of refractory symptomatic dural venous sinus thrombosis.